Heterozygous p.I171V mutation of the NBN gene as a risk factor for lung cancer development - KAŁUŻNA, EWELINA MARIA (Oncol Lett, 2015)
The NBN gene, also known as NBS1, is located on the chromosome band 8q21.3, and encodes a 754-amino acid-long protein named nibrin. This protein is a member of the MRE1-RAD50-NBN nuclear complex, and is involved in numerous cell processes essential for maintaining genomic stability. Heterozygous variants in the NBN gene, including p.I171V, c.657del5 and p.R215W, have been described as risk factors for the development of several malignancies. However, there is no report regarding the association of these mutations with lung cancer thus far. Therefore, the present study aimed to evaluate whether there is an association between the heterozygous p.I171V, c.657del5 and p.R215W variants of the NBN gene and the risk of developing lung cancer. The frequency of these variants was estimated in a group of 453 adults diagnosed with non-small cell lung cancer (NSCLC) and in healthy controls (2,400 for p.I171V, 2,090 for c.657del5 and 498 for p.R215W). The p.I171V variant was assessed by restriction fragment length polymorphism analysis of polymerase chain reaction (PCR) products, using MunI (MfeI) restriction enzyme, whereas the c.657del5 and p.R215W variants were assessed by the PCR single-strand conformation polymorphism method. A significantly increased risk of developing lung cancer was observed for the p.I171V variant, which was present in 17 (3.75%) of the 453 cases of lung cancer and in 12 (0.5%) of the 2,400 healthy individuals (odds ratio, 7.759; P<0.0001). The results obtained indicated an association between the p.I171V mutation and the development of lung cancer. Therefore, this variant may be considered a risk factor for NSCLC. Prospective studies with larger groups of patients may reveal the potential impact of the p.I171V variant in the occurrence of lung cancer.